The Potential Role of circRNA in Tumor Immunity Regulation and Immunotherapy - Xu, Zihao; Li, Peiyao; Fan, Li; Wu, Minghua (Frontiers in Immunology, 2018)
Non-coding RNAs (ncRNAs) can be divided into circular non-coding RNAs (circRNAs) and linear non-coding RNAs. ncRNAs exist in different cell types, including normal cells, tumor cells and immunocytes. Linear non-coding RNAs, such as long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), have been found to play important roles in the regulation of tumor immunity and immunotherapy; however, the functions of circRNAs in tumor immunity and immunotherapy are less known. Here, we review the current status of ncRNAs in the regulation of tumor immunity and immunotherapy and emphatically discuss the potential roles of circRNAs as tumor antigens in the regulation of tumor immunity and immunotherapy.